Pirfenidone: An Encouraging Therapeutic Approach For Enhancing Lateral Spinothalamic Tract Function After Spinal Cord Compression Injury - Noman Ullah Wazir; Ambereen Humayun; Irum Javaid; Asma Amir; Nayyab Khattak; Ayesha Iftikhar (Journal of Rawalpindi Medical College)
Abstract